2006
DOI: 10.2337/dc06-0654
|View full text |Cite
|
Sign up to set email alerts
|

Cystic Fibrosis–Related Diabetes

Abstract: OBJECTIVE -Cystic fibrosis (CF)-related diabetes has been regarded as a mild form of diabetes with a low risk of severe diabetes complications. The prevalence of CF-related diabetes increases with age, resulting in a 50% prevalence of diabetes at age 30 years. We sought to investigate whether microvascular complications in CF-related diabetes appear with a relevant frequency.RESEARCH DESIGN AND METHODS -Thirty-eight patients aged 30 (range 18 -55) years with CF-related diabetes for 20 (0 -31) years were screen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
71
1
1

Year Published

2007
2007
2015
2015

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 75 publications
(74 citation statements)
references
References 15 publications
1
71
1
1
Order By: Relevance
“…In Denmark, 36% of the patients who have had diabetes for over 10 years present retinopathy (55). A study that evaluated 285 patients with CFRD did not find complications in patients who presented normal fasting glycemia.…”
Section: Macro and Microvascular Complicationsmentioning
confidence: 99%
“…In Denmark, 36% of the patients who have had diabetes for over 10 years present retinopathy (55). A study that evaluated 285 patients with CFRD did not find complications in patients who presented normal fasting glycemia.…”
Section: Macro and Microvascular Complicationsmentioning
confidence: 99%
“…retinopathy, neuropathy and nephropathy) occur in patients with CFRD. 66,67 Yung et al, 63 albeit in a small study, reported a prevalence of retinopathy among patients with CFRD who had been diagnosed for 5 years or more of 16% (5 out of 31 patients) and among those who had been diagnosed for 10 years or more of 23% (3 out of 13 patients). The prevalence of nephropathy was between 3% and 16% and of peripheral neuropathy between 5% and 21%.…”
Section: Complicationsmentioning
confidence: 99%
“…3,19,36 KF'de hipoalbüminemi karaciğer tutulumuna, pankreas etkilenmesi sonucu malabsorbiyona ve malnütrisyona bağlı gelişebilir. İlk başvuruda hipoalbüminemi %4-50 oranında bulunmuş ve hipoalbümineminin ciddi solunum sistemi semptomları ile korele olduğu bildirilmiştir.…”
Section: Discussionunclassified